2011
DOI: 10.1369/0022155411404704
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Immunohistochemistry on Molecular Analysis of Tissue Samples

Abstract: The field of molecular pathology has advanced over the past 15 years with the integration of laser-based microdissection systems and a variety of associated biological assays and analysis methods (Bonner et al. 1997; EmmertBuck et al. 1996;Burgess and Hazelton 2000;Iyer and Cox 2010;Craven and Banks 2001;Mustafa et al. 2008;Lawrie and Curran 2005;Charboneau et al. 2002;Gillespie et al. 2004;Bichsel et al. 2001;Callagy et al. 2005;Kurihara et al. 2002) SummaryLaser-based tissue microdissection is an important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 48 publications
0
25
0
Order By: Relevance
“…Microdissected tissue pieces can also be investigated after their status linked to markers of interest. This approach was named immune laser capture microdissection (iLCM), where IHC is performed (Fend et al, 2000;Tangrea et al, 2011) prior to LCM. It was used for multiple clinical applications such as proteomic studies of prolactin cells from pituitary adenoma (Liu et al, 2010) or CD24 + / -cells from pancreatic adenocarcinoma, this marker being directly correlated to cancerous tumorigenesis, progression, and metastasis of pancreatic cancer (Zhu et al, 2013).…”
Section: Laser Capture Microdissection (Lcm)mentioning
confidence: 99%
“…Microdissected tissue pieces can also be investigated after their status linked to markers of interest. This approach was named immune laser capture microdissection (iLCM), where IHC is performed (Fend et al, 2000;Tangrea et al, 2011) prior to LCM. It was used for multiple clinical applications such as proteomic studies of prolactin cells from pituitary adenoma (Liu et al, 2010) or CD24 + / -cells from pancreatic adenocarcinoma, this marker being directly correlated to cancerous tumorigenesis, progression, and metastasis of pancreatic cancer (Zhu et al, 2013).…”
Section: Laser Capture Microdissection (Lcm)mentioning
confidence: 99%
“…Thus, computer-aided IHC (TTF-1) LCM ensured we identified the majority of tumor cells (single cells as well as clusters of tumor cells) and increased our specificity. While this provided a high-throughput semiautomated method to isolate tumor cells for molecular assays, the downside is that IHC can negatively affect the DNA recovered from tissue sections [30]. …”
Section: Limitationsmentioning
confidence: 99%
“…Studies from our group and others have shown that, although the quantity of DNA retrieved is reduced, the quality and integrity is not affected and DNA can be successfully amplified by PCR [30] with no obvious difference in performance between IHC-stained and unstained samples. However, in the context of clinical molecular assays one does have to be cautious of introducing false-positive results when amplifying very small amounts of DNA.…”
Section: Limitationsmentioning
confidence: 99%
See 2 more Smart Citations